2004
DOI: 10.1021/mp049964d
|View full text |Cite
|
Sign up to set email alerts
|

Micellar Aggregation and Membrane Partitioning of Bile Salts, Fatty Acids, Sodium Dodecyl Sulfate, and Sugar-Conjugated Fatty Acids:  Correlation with Hemolytic Potency and Implications for Drug Delivery

Abstract: The co-administration of a drug with a penetration enhancer (PE) is one method by which the membrane permeability of a drug can be improved. To facilitate PE design, it is important that the molecular basis of PE toxicity and efficacy be examined, so we investigated the membrane affinity and micellar aggregation of a series of synthetic liposaccharide PEs and correlated these properties with hemolytic potency. The influence of liposaccharide alkyl chain length (nc) on the system was studied, and comparisons we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 64 publications
2
25
0
Order By: Relevance
“…It is important to do this because numerous papers deal with the toxicity of the excipients used in this study and all come to a similar conclusion, stating that lower level of excipient results in a lower level of toxicity (1,(29)(30)(31). Toxic effects of surfactants are associated with their interaction with biological membranes, and as such are proven to exert hemolytic effect (32). Based on such publications and assessing the benefit/risk ratio of each excipient, it was concluded that the amount of excipient to be reduced first and foremost should be polysorbate 80, followed by the reduction of the concentration of ethanol.…”
Section: Optimizing the Concentration Of Excipientsmentioning
confidence: 76%
“…It is important to do this because numerous papers deal with the toxicity of the excipients used in this study and all come to a similar conclusion, stating that lower level of excipient results in a lower level of toxicity (1,(29)(30)(31). Toxic effects of surfactants are associated with their interaction with biological membranes, and as such are proven to exert hemolytic effect (32). Based on such publications and assessing the benefit/risk ratio of each excipient, it was concluded that the amount of excipient to be reduced first and foremost should be polysorbate 80, followed by the reduction of the concentration of ethanol.…”
Section: Optimizing the Concentration Of Excipientsmentioning
confidence: 76%
“…To test the hypothesis that the antibacterial activities of the acylpolyamines are a consequence of membrane permeabilization due to their cationic amphipathic nature, we sought to correlate the surface activity of these compounds with hemolytic potency (42). Erythrocyte damage was measured using two different techniques.…”
Section: Vol 50 2006 Membrane Permeabilization By Acylhomosperminesmentioning
confidence: 99%
“…It is described that the microdomains contained in the mixed micelles were able to solubilise cholesterol [10][11][12][13][14]. An important aspect in the formation of mixed micelles lies in the fact that the mixed micelle association lowers the monomeric activity of bile salts and thus prevents the solubilisation and thus destruction and membranolytic effect of the apical membrane of the epithelial cells [15,16]. Table 1.…”
Section: Introductionmentioning
confidence: 99%